1994
DOI: 10.1046/j.1365-313x.1994.06030441.x
|View full text |Cite
|
Sign up to set email alerts
|

The firefly luciferase gene as a non‐invasive reporter for Dendrobium transformation

Abstract: Here a screening method is described for transformed tissues and transgenic plants of Dendrobium (Orchidaceae) using the firefly luciferase gene (luc) as a combined marker/reporter gene. Protocorm‐likebodies (PLB) were bombarded with tungsten particles (1.3 µm) coated with plasmids carrying a 35S‐luc chimeric gene. Three weeks after bombardment 1 mM luciferin was added to the tissues and transformed cells were identified by virtue of their bioluminescence as monitored by low‐light video microscopy in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 0 publications
0
39
0
6
Order By: Relevance
“…A reproducible methodology for the genetic transformation of orchids, and better recognition of the factors affecting the transformation process, are needed in order to support this objective. Previous studies have reported orchid transformation either directly through the delivery of marker genes such as those encoding Escherichia coli β-glucuronidase (GUS) and Aequorea victoria green fluorescent protein (GFP) into plant cells by particle bombardment (Anzai et al, 1996), or indirectly through the use of A. tumefaciens (Belarmino and Mii, 2000;Chia et al, 1994;Mishiba et al, 2005;Chan et al, 2005;. Recently, we developed a convenient method for genetic modification of Phalaenopsis amabilis orchids using A. tumefaciens (Semiarti et al, 2007) in which intact protocorms (young orchid seedlings) were used for transformation.…”
Section: Transformation Of Phalaenopsis Amabilis (L) Blumementioning
confidence: 99%
“…A reproducible methodology for the genetic transformation of orchids, and better recognition of the factors affecting the transformation process, are needed in order to support this objective. Previous studies have reported orchid transformation either directly through the delivery of marker genes such as those encoding Escherichia coli β-glucuronidase (GUS) and Aequorea victoria green fluorescent protein (GFP) into plant cells by particle bombardment (Anzai et al, 1996), or indirectly through the use of A. tumefaciens (Belarmino and Mii, 2000;Chia et al, 1994;Mishiba et al, 2005;Chan et al, 2005;. Recently, we developed a convenient method for genetic modification of Phalaenopsis amabilis orchids using A. tumefaciens (Semiarti et al, 2007) in which intact protocorms (young orchid seedlings) were used for transformation.…”
Section: Transformation Of Phalaenopsis Amabilis (L) Blumementioning
confidence: 99%
“…In Dendrobium orchids, genetic transformation studies has been initiated by using biolistic-mediated method (Chia et al 1994;Kuehnle and Sugii 1992;Tee et al 2003;Suwanaketchanatit et al 2007), followed by Agrobacterium-mediated method (Men et al 2003). Among these studies, successful regeneration of transgenic plants has been reported by Men et al (2003) and Suwanaketchanatit et al (2007).…”
mentioning
confidence: 99%
“…Consequently, genetic transformation method is expected to apply for transferring disease resistance genes as an alternative procedure. So far, transformation with direct delivery of marker genes such as GUS and GFP genes into plant cells by particle bombardment and indirectly through the use of Agrobacterium-mediated procedure has been reported on orchids (Anzai et al 1996;Belarmino and Mii 2000;Chia et al 1994). However, there have been no reports on the transformation of useful genes including plant disease resistance genes into Phalaenopsis.…”
mentioning
confidence: 99%